Challenges of Economics Teachers in Implementing the Merdeka Curriculum - Muhammad Muhlis; Noviana Mariatul Ulfa; Arie Eko Cahyono (Al-Qalam Institue, 2025)
The Independent Curriculum aims to provide greater learning flexibility by accommodating students’ individual needs and potential. However, its implementation often poses challenges for teachers, particularly in adapting pedagogical practices to the demands of the curriculum. This study analyzes the difficulties economics teachers face in implementing the Independent Curriculum within the Jember Regency Economics MGMP forum. This research employed a descriptive qualitative approach. Four informants were selected, consisting of the MGMP Chair, the Deputy Chair of the Development Division, and two economics teachers. Data were collected through interviews, observations, and documentation, then analyzed through data collection, validation, presentation, and conclusion drawing. Triangulation was used to ensure data validity. Findings show that teachers experience several obstacles, including limited understanding of differentiated instruction, difficulties adapting learning materials, challenges developing appropriate assessment methods and curriculum-aligned learning tools, constraints on integrating the Pancasila Student Profile into project-based themes, and suboptimal use of the Merdeka Teaching Platform. These challenges reflect gaps in curriculum readiness, teacher competency development, and institutional support. Strengthening continuous professional development, intensive mentoring, and school-level facilitation is essential to improve curriculum implementation.